Analysis of the Interaction Between Responsible Leadership and Perceived Training Benefits on Planner Ability - Ivan Budi Susetyo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
World issues related to SDGs, this training is a solution to overcome global challenges. The First Functional Training of Expert Planners at LPPM Unhas and Pusbindik latren Bappenas increased the capacity of Indonesian expert planners. Previous research only focused on one variable, such as Perceived Training Benefit (PTB) or Responsible Leadership (RL), without considering the interaction of variables and their influence on planner competence. This research proposes a comprehensive pseudo-moderation model to investigate the relationship between PTB, RL, and Planning Competency (KP) in an e-learning context. The research design used quantitative analysis of online surveys and interviews and pseudo-moderation was carried out using multiple linear regression. The Responsible Leadership (Z) variable has a significant influence on the Planner Competence (Y) variable with a regression coefficient of 1.096. Perceived Training Benefit (X) does not have a significant influence on the Planner Competence variable (Y). There is a positive interaction between Perceived Training Benefit (X) and Responsible Leadership (Z) which influences the Planner Competence (Y) variable. The beta coefficient value for Responsible Leadership (Z) is 0.724, indicating that RL has the strongest positive influence on the dependent variable. The interaction between Perceived Training Benefit (X) and Responsible Leadership (Z) has the most significant influence on the dependent variable. This research contributes to LPPM Unhas and other organizations that organize planner training to increase the effectiveness of their training. By understanding the factors that influence PTB and KP, organizations can design training programs that are more effective and relevant to planners' needs.